The Effect of Training With Loaded Rackets On The Development Of Force Momentum And Straight Forehand In Badminton - Abdul Hussein, Naiem; Ibrahim, Hudifa (Journal of Physical Education, 2017)
The problem of the research lies in weakness in straight forehand stroke innational badminton league athletes. This skill requires strength and high speed to beperformed correctly thus force momentum of the hitting arm should be increased. Theresearch aimed at designing special exercises using loaded rackets to develop forcemomentum for the hitting arm while performing straight forehand by national badmintonleague athletes. The researchers used the experimental method. The subjects were (6)national badminton athletes. Pre tests included hitting arm tests followed by the trainingprogram with two training sessions per week for six weeks. The data was collected andtreated using proper statistical operations. The researchers concluded that the tests showedgreat results in favor of posttests of accuracy and force momentum. Finally the researchersrecommended using loaded weights on other variables for badminton athletes